Open Data Sources for Species Distribution Modelling: Biodiversity Information Systems and Spatial Datasets of Environmental Conditions Variables - Maxim Shashkov (Пернатые хищники и их охрана)
Any species distribution modelling method requires two types of input data: (1) occurrences of the focal species, represented as a set of points with geographic coordinates; and (2) environmental variables (predictors) that may be valuable for species distribution, in the format of continuous raster layers. Considerable advances in the digitization of scientific collections around the globe and development of other sources for species distribution data have made it possible for researchers to significantly augment their own data to develop more accurate models.